Pelaksanaan Comprehensive Health School Model (CHSM) Untuk Pencegahan Penularan Covid-19 di Sekolah Dasar - Fajarina Lathu Asmarani; Endang Nurul Syafitri; Sindi Fazri Fatmasari (STIKes Payung Negeri Pekanbaru, 2022)
The Joint Decree of four ministers allows face-to-face learning in 2021. The opening of schools during a pandemic can lead to school clusters. So it is necessary to identify the prevention of COVID 19 transmission in schools with the Comprehensive Health School Model approach. The purpose of this study was to identify the implementation of CHMS for the prevention of COVID-19 in schools. This type of research is quantitative research with a descriptive approach. The population in this study is the State Elementary School in Ngemplak District is 22 with total sampling. The Comprehensive Health School Model is a series of activities carried out by schools in terms of the Social and Physical Environment, Teaching and Learning, Health School Policy, Partnership, and Services to prevent the transmission of COVID 19 in schools. Data were taken using a questionnaire and analyzed using univariate analysis. The results show that all schools can carry out teaching and learning components, school health policies, and partnership services. In the social and physical environment components, three sub-variables have not been implemented, namely the physical environment where windows and ventilation are still open, the distance from the bench in the office is at least 1 m and there is no room disinfectant available. It can be concluded that all State Elementary Schools in Ngemplak Sleman District have implemented all components of the Comprehensive Health School Model except the Physical Environment. So that it can be recommended for public elementary schools to carry out three sub-variables that have not been implemented and the